Efektifitas Penggunaan Buku Pelajaran Aqida Akhlak Kelas VIII Dalam Meningkatkan Motivasi Belajar Siswa Di MTs Babussalam Waisakai - Usia, Rakiba; Umasugi, Marwa (Peneliti.net, 2025)
This study aims to improve students’ learning motivation through the use of the Akidah Akhlak textbook based on the 2013 Curriculum among eighth-grade students at MTs Babussalam Waisakai. The research employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, action, observation, and reflection phases. Data were collected through observation, interviews, and documentation, and analyzed qualitatively using the Miles and Huberman model. The findings indicate a significant increase in students’ learning motivation, demonstrated by higher levels of activeness, questioning, discussion participation, and understanding of the material. The use of textbooks combined with discussion and contextual approaches effectively stimulated interest and supported the internalization of moral values. Thus, printed textbooks remain relevant and effective learning media for enhancing students’ motivation and character.